Dyke Award. Imaging of Spinal CSF Pulsation by 2DFT MR: Significance During Clinical Imaging - Rubin, Jeremy B.; Enzmann, Dieter R. (American Journal of Neuroradiology, 1987)
Understanding the MR appearance of spinal CSF is important in interpreting clinical spine images because the diagnosis of spinal pathology requires an accurate delineation of spinal CSF from spinal cord and thecal sac. During conventional 2DFT MR imaging of the spine, CSF pulsation caused two interdependent flow phenomena, signal loss and phase-shift images. Signal loss was observed as decreased signal intensity arising from pulsatile spinal CSF. Phase-shift images were observed as signal intensity arising from and morphologically identical to the spinal subarachnoid space but symmetrically displaced from it along the phase-encoding axis of MR images, either added to or subtracted from stationary signal intensity. These phenomena were common, occurring in most cervical and thoracic long-TR images. Both phenomena were less apparent in the lumbar region in most cases. CSF pulsation flow phenomena decreased CSF-spinal cord and CSF-thecal sac conspicuity, thereby obscuring normal and pathologic anatomy and, at times, simulating pathology. The areas of signal loss showed variable but characteristic patterns in the cervical and thoracic spine corresponding to regions of greatest flow. Signal loss in the axial plane was more pronounced when thin slices were used. Phase-shift images degraded overall image quality secondary to spatial mismapping of spinal CSF signal intensity. With the use of CSF gating, both signal loss and phase-shift images were eliminated. Understanding these features will be important in the accurate interpretation of MR spine images because analysis of CSF pulsation flow phenomena provides physiologic and pathologic information, and awareness of their existence avoids diagnostic confusion.